Implementation of electroencephalography controlled prosthetic hand. (2018) - Rizvi, Syed Tahir Hussain; Karim, Mansoor; Gulzar, Muhammad Majid; Javed, Muhammad Yaqoob; Furqan, Muhammad
The purpose of brain machine interface (BMI) is to provide a communication path between brain signals and external devices. Use of brain signals for restoring function of impaired body parts using scientific methods require brain machine interface. This article presents BMI to control five-fingered prosthetic hand using the electroencephalography (EEG) signals. The core objective of the system is to develop a control system that will be able to communicate with the brain thoughts. EEG signals captured from the human scalp are used as information carrier for brain control interface (BCI) system. This research article discusses the development of a system to assist disable persons using EEG based signals.